2022
DOI: 10.3389/fvets.2022.867784
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Bacteria Isolated From Canine Urine Samples Submitted to a Veterinary Diagnostic Laboratory, Illinois, United States

Abstract: The emergence of antimicrobial resistance (AMR) in dogs constitutes a threat to animal and human health. There is a lack of studies in Illinois that evaluated the prevalence of AMR among urinary bacterial pathogens. In the study, we included 803 isolates (299 Gram-positive and 504 Gram-negative) that were isolated from 2,583 canine urine samples submitted to the Veterinary Diagnostic Laboratory, the University of Illinois between 2019 and 2020 from dogs suspected of urinary tract infections (UTI). The most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 53 publications
7
18
1
Order By: Relevance
“…Escherichia coli is the most common bacteria responsible for UTIs in dogs and cats in Europe [ 22 , 23 ], the USA [ 19 ], Canada [ 30 ], and New Zealand [ 31 ]. The same result was reported in the most recent studies carried out in the USA [ 32 , 33 ], the UK [ 17 ], Spain [ 34 ], Italy [ 27 ], and Germany [ 35 ]. Cephalosporins resistance above 30% was detected in E. coli isolated from dogs and cats.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Escherichia coli is the most common bacteria responsible for UTIs in dogs and cats in Europe [ 22 , 23 ], the USA [ 19 ], Canada [ 30 ], and New Zealand [ 31 ]. The same result was reported in the most recent studies carried out in the USA [ 32 , 33 ], the UK [ 17 ], Spain [ 34 ], Italy [ 27 ], and Germany [ 35 ]. Cephalosporins resistance above 30% was detected in E. coli isolated from dogs and cats.…”
Section: Discussionsupporting
confidence: 86%
“…This bacterium is of particular interest considering its intrinsic resistance to different antibiotics and its acquired fluoroquinolone resistance, as described several times in the abovementioned studies. In the present study, the resistant profile observed for P. mirabilis was also characterized by the resistance to imipenem, as recently reported in the USA [ 33 ]. These data raise concerns regarding the potential zoonotic role of UTI-related P. mirabilis strains isolated in the present study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations